The past, present, and future of research on neuroinflammation-induced mild cognitive impairment: A bibliometric analysis - Cai, Ming; Zhang, Yuanqi; Chen, Si; Wu, Zhan; Zhu, Lei (Frontiers in Aging Neuroscience, 2022)
Background Mild cognitive impairment (MCI) is a precursor to dementia, and neuroinflammation in the brain is thought to be one of the main pathogenic mechanisms of MCI. However, the underlying neurobiological mechanisms have not been fully explored. The purpose of this study was to establish a visual model map of the articles in the field of neuroinflammation-induced MCI over the past 11 years to reveal the research hotspots and predict the future development trends in this field, which will help to promote the research and development for MCI. Methods The “neuroinflammation” and “mild cognitive impairment” were used as search terms, and literature about neuroinflammation-induced MCI published between 2011 and 2021 was collected from the Web of Science. CiteSpace and VOSviewer were used to create visual model maps, and assess collaboration among different authors, countries, and institutions. Finally, the current research hotspots and future research directions were analyzed by using high-frequency keywords analysis and co-cited reference burst analysis. Results A total of 226 articles were retrieved. The number of publications in neuroinflammation-induced MCI shows an upward trend. Since 2018, the number of papers published in this field has increased significantly, with an average of more than 100 published each year. The United States had the highest literature production and the number of cited journals in this research area, and the National Institute on Aging was the most productive research institution. Brooks D.J. and Heneka M.T. had the highest number of publications and had the highest frequency of co-citations. The co-cited references revealed the evolution of the research themes, and the current studies are mainly focused on the effects of various metabolites on the control of microglial activation. “Cerebrospinal fluid”, “mouse model”, “tau”, “microglial activation”, “astrocytes”, and “TREM2” were the current high-frequency and emerging keywords. Conclusion Research on neuroinflammation-induced MCI is burgeoning, and the close collaboration with different nations and institutions need to be further strengthened. Current research hotspots are focused on the effects of various metabolites on microglia activation. Future studies should focus on how to regulate the phenotypes of microglia and astrocyte to reduce neuroinflamation and treat MCI.